2013
DOI: 10.1016/j.jtcvs.2013.02.018
|View full text |Cite
|
Sign up to set email alerts
|

Durability of left ventricular assist devices: Interagency Registry for Mechanically Assisted Circulatory Support (INTERMACS) 2006 to 2011

Abstract: The Analysis of Interagency Registry for Mechanically Assisted Circulatory Support data showed greater durability for continuous flow than for pulsatile left ventricular assist devices. Even longer durations of support can be expected if pump durability continues to improve.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
33
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(34 citation statements)
references
References 16 publications
0
33
0
1
Order By: Relevance
“…In this context, the advent of implantable left ventricular assist device (LVAD) 51 represents a major medical progress for end-stage heart failure in selected patients [7,8], and 52 is currently used as a bridge-to-heart transplantation, a bridge-to-recovery, or as destination 53 therapy (i.e., as the last resort in patients with neither perspectives of recovery, nor heart 54 transplant). Implantable LVAD intended for long-term use rely on a percutaneous driveline, 55 to carry electric signals and energy from the controller and batteries to the implanted pump.…”
mentioning
confidence: 99%
“…In this context, the advent of implantable left ventricular assist device (LVAD) 51 represents a major medical progress for end-stage heart failure in selected patients [7,8], and 52 is currently used as a bridge-to-heart transplantation, a bridge-to-recovery, or as destination 53 therapy (i.e., as the last resort in patients with neither perspectives of recovery, nor heart 54 transplant). Implantable LVAD intended for long-term use rely on a percutaneous driveline, 55 to carry electric signals and energy from the controller and batteries to the implanted pump.…”
mentioning
confidence: 99%
“…We conducted a semi-systematic review, which revealed that the target paper disappeared for certain items when the research quality conditions were narrowed down; therefore, we removed these conditions and chose 6 reports related to events [11][12][13][14][15][16]. We additionally selected 2 Japanese reports on re-hospitalization [17,18], which has a large impact on the health care system but could not be found in our current review.…”
Section: Long-term Prognosis Of Cost Effectivenessmentioning
confidence: 99%
“…[1][2][3] With their approval for use as destination therapy (DT) and the improvement in mechanical durability of the newer devices, average support times have surpassed 12 months, 1,3,4 and device exchange owing to complications will inevitably be required for a variety of indications. 5,6 Although uncommon, device malfunction requiring replacement is a serious and potentially fatal complication. 2,5 Several risk factors have been identified, such as the use of first-generation devices, obesity, older age and renal failure.…”
mentioning
confidence: 99%
“…5,6 Although uncommon, device malfunction requiring replacement is a serious and potentially fatal complication. 2,5 Several risk factors have been identified, such as the use of first-generation devices, obesity, older age and renal failure. 1,7 To our knowledge, no Canadian centre has reported on their experience with these cases, thus far.…”
mentioning
confidence: 99%